Is Itch Intensity in Atopic Dermatitis Associated with Skin Colonization by Staphylococcus aureus? - Blicharz, Leszek (Indian J Dermatol, 2020)
BACKGROUND: Atopic dermatitis (AD) is a highly pruritic skin condition of unclear pathogenesis. Patients with AD are predisposed to colonization by Staphylococcus aureus due to deficiencies in the mechanical and immunological functions of the skin barrier. Recent studies indirectly show that S. aureus may aggravate disease flares in AD. AIMS: The aim was to assess the relationship between S. aureus skin colonization and itch intensity in patients with AD. MATERIALS AND METHODS: The SCORAD index components reflecting itch intensity (excoriations, subjective evaluation of pruritus, and sleep loss) were assessed in 33 adult patients with AD. Swabs were taken from lesional and nonlesional skin. The prevalence and abundance of S. aureus were assessed. Statistical analysis was performed to correlate the microbiological results with the clinical parameters. The control group consisted of 36 healthy volunteers. RESULTS: Lesional and nonlesional skin showed a high frequency of S. aureus colonization when compared with controls (81.8% and 57.6% vs 5.6%, respectively, P < 0.0001). The mean concentration (points) of S. aureus was 2.01 ± 1.25, 1.06 ± 1.14, and 0.11 ± 0.46, respectively (P < 0.0001). S. aureus abundance on lesional/nonlesional skin positively correlated with excoriations and sleep loss (rho = 0.69, P < 0.00001; rho = 0.44, P < 0.01; rho = 0.41, P < 0.02; and rho = 0.34, P < 0.05, respectively). The mean values of excoriations were higher in patients colonized by S. aureus than in patients without S. aureus carriage. CONCLUSION: S. aureus skin colonization may be one of the factors aggravating itch in AD. It may be hypothesized that restoring the natural composition of the skin microbiome may reduce pruritus intensity.